Sistem Administrasi dan Pelayanan Warga Berbasis Web dengan Algoritma Queue di RW 10 Rawabugel Kota Bekasi - Wahyu Syafriadi; Achmad Noeman; Mayadi (Journal of Informatic and Information Security, 2026)
The administrative and community service processes in RW 10 Rawabugel, Bekasi City, are still carried out manually, resulting in delays in service, long queues, and difficulties in managing community data and archives. Therefore, a system is needed to improve the efficiency and quality of service. This study aims to design and develop a web-based administrative and community service system by applying the Queue algorithm using the First Come First Served (FCFS) method. This system allows residents to submit service requests online and monitor the status of their requests in real time, while RW officials can manage data and archives in a structured and computerized manner. The use of the Queue algorithm serves to automatically and fairly arrange the order of services based on the time of submission. The results of the study show that the developed system has succeeded in increasing service efficiency, reducing queue backlogs, and facilitating the management of resident administrative data. This system is expected to be a solution in improving the quality of administrative services in the RW environment.